Importaç\~oes agropecuárias Brasileiras: Uma avaliaç\~ao dos produtos líderes no período 1989-2012 - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The mean goal of the study was to map food products that are constant or regular in Brazilian imports during 1989-2012 periods. Analyzing Brazilian agricultural imports face to Brazilian total imports it is possible to observe a decreasing cost of food imports in terms of Brazilian imports. Moreover, the study highlights big share of specific products in Brazilian agricultural imports, that is, at first, edible vegetables and certain roots, cereals, edible fruits and nuts, and animal or vegetable fats and oils; at second, dairy products, beverages, spirits and vinegar, live animals, meat and edible meat offal, oil seeds and oleaginous fruits, preparations of vegetables, and miscellaneous edible preparations. Future questions can include, for example, similar analyses at level of agricultural inputs employed in Brazil. Moreover, it would be useful to investigate if it is worth for Brazil boost internal production in the case of non-regular imports of foods.
Keywords: F14; Q11; Q17; 330; farming and castle raising; imports; Brazil